Erotic Začinka-Poem of the 17th Century - Tatarin, Milovan (Poznańskie Studia Slawistyczne, 2018)
Paper focuses on a poem Mlad užežen u ljubavi, preserved in an early manuscript by Dubrovnikʼs merchant Miho Martellini, created before 1657. This is the most erotic začinka-poem of the 17th century, inspired by the so called cushion customs. The above mentioned poem is a part of a corpus created parallel with the official literary production, and its existence demonstrates the stratification of the 17th century literature, and marks the existence of thematically and stylistically pure folk literature, together with epics, epic poems, tragedies and tragicomedies. That sort of literature didnʼt have to change the readers, to instruct them in virtuous life, not even to give them some aesthetic pleasure. Its purpose was primarily entertainment.